Skladenjske razlike v katekizmih slovenskih in hrvaških reformatorjev - Orel, Irena (Slavia Centralis, 2019)
The article presents linguistic differences on syntactic levels in selected and essentially identical Slovenian and Croatian translations of texts from 16th Century catechisms: from the sermon of faith in Primož Trubar's Catechism (1550) and the Croatian-Latin edition by Štefan Konzul (1564) as well as the Carniolan and Croatian translation (allegedly by Matthias Flacius Illyricus) of the school catechism by Sebastijan Krelj in the Children's Bible (Otročja biblija) (1566). The hypothesis to be verified is whether the Croatian texts, despite the possible influence of the Slovenian version on them, do not contain (as many) Germanic syntactic structures as the Slovene texts.
Keywords: 16. st.; 16th cent.; catechisms; contrastive analysis; Croatian reformation; Flacius Illyricus, Matthias; historical syntax; hrvaška reformacija; katekizmi; kontrastivna analiza; Konzul Istranin, Stjepan; Krelj, Sebastijan; Slovene language; Slovenian reformation; slovenska reformacija; slovenščina; the history of Slovene language; Trubar, Primož; zgodovina slovenskega knjižnega jezika; zgodovinska skladnja